A combinatorial auction mechanism for time-varying multidimensional resource allocation and pricing in fog computing - Li, Shiyong; Zhang, Yanan; Sun, Wei; Liu, Jia (Zielona Góra: Uniwersytet Zielonogórski)
It is a hot topic to investigate resource allocation in fog computing. However, currently resource allocation in fog computing mostly supports only fixed resources, that is, the resource requirements of users are satisfied with a fixed amount of resources during the usage time, which may result in low utility of resource providers and even cause a waste of resources. Therefore, we establish an integer programming model for the time-varying multidimensional resource allocation problem in fog computing to maximize the utility of the fog resource pool.
Keywords: fog computing; combinatorial auction; time-varying multidimensional resource allocation; resource pricing